2021
DOI: 10.3390/pharmaceutics13101604
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Inhibition in Relapsed/Refractory Leukemia and Lymphoma Settings: Recent Prospects into Clinical Investigations

Abstract: Cancer is still a major barrier to life expectancy increase worldwide, and hematologic neoplasms represent a relevant percentage of cancer incidence rates. Tumor dependence of continuous proliferative signals mediated through protein kinases overexpression instigated increased strategies of kinase inhibition in the oncologic practice over the last couple decades, and in this review, we focused our discussion on relevant clinical trials of the past five years that investigated kinase inhibitor (KI) usage in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 161 publications
(220 reference statements)
0
6
0
Order By: Relevance
“…Anthracyclines, including Adriamycin (doxorubicin), Adriamycin liposomes, and daunorubicin, are widely used in the treatment of various malignant tumors, and clinical trials of these drugs began in the 1960s. The cardiotoxic effects of anthracyclines were first identified by Machado et al ( 13 ) in a clinical trial involving 94 patients (68 children and 26 adults) with various tumor types. This trial summarized the clinical experience with daunorubicin ( 13 ).…”
Section: Chemotherapeutic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthracyclines, including Adriamycin (doxorubicin), Adriamycin liposomes, and daunorubicin, are widely used in the treatment of various malignant tumors, and clinical trials of these drugs began in the 1960s. The cardiotoxic effects of anthracyclines were first identified by Machado et al ( 13 ) in a clinical trial involving 94 patients (68 children and 26 adults) with various tumor types. This trial summarized the clinical experience with daunorubicin ( 13 ).…”
Section: Chemotherapeutic Drugsmentioning
confidence: 99%
“…The cardiotoxic effects of anthracyclines were first identified by Machado et al ( 13 ) in a clinical trial involving 94 patients (68 children and 26 adults) with various tumor types. This trial summarized the clinical experience with daunorubicin ( 13 ). Ewer et al ( 14 ) reported the cardiovascular adverse effects of anthracyclines in a multicenter retrospective analysis of 4,018 patients.…”
Section: Chemotherapeutic Drugsmentioning
confidence: 99%
“…Regardless of being intrinsic or acquired, MDR pathways provide tumors with the ability to bypass the effects of proliferation and survival impairment imposed by cytotoxic treatments through mechanisms such as increased drug efflux caused by overexpression of the transmembrane transporters of the ATP binding cassette (ABC) family, upregulation of DDR proteins, epigenetic alterations modifying oncogene expression, and tumor microenvironment alterations [ 14 , 15 ].…”
Section: Background Of Cancer Managementmentioning
confidence: 99%
“…The need to avert the highly toxic profiles of conventional chemo-immunotherapy and to overcome the emerging cases of tumor MDR has fueled a growing interest in the field of precision medicine and targeted molecular therapies in the last couple of decades. Although relatively new alternatives in oncologic practice, the increased specificity and the positive clinical outcomes achieved through targeted molecular therapies have already consolidated them as a promising prospect for the future of cancer management [ 15 , 16 ].…”
Section: Background Of Cancer Managementmentioning
confidence: 99%
“…TK inhibitors compete with ATP for the ATP binding site of the receptor, affecting protein phosphorylation and thus significantly reducing intracellular signaling and CML progress ( Rosti et al, 2017 ; Jiao et al, 2018 ). However, mutations in the ATP binding site leading to intrinsic and extrinsic mechanisms of drug resistance led to therapy failure, requiring the development of second and third generations of TKIs, such as nilotinib, dasatinib, bosutinib, and ponatinib to overcome the resistance in patients with CML ( Pophali and Patnaik, 2016 ; Machado et al, 2021 ). Therefore, it is imperative to develop studies seeking new molecules or redirect already known drugs to target the BCR-ABL protein with potential application in the CML.…”
Section: Introductionmentioning
confidence: 99%